M-Health Apps and Physical and Mental Health Outcomes of Sexual Minorities - Nick Drydakis (Global Labor Organization (GLO), 2022)
Given the assigned health inequalities faced by sexual minorities, it is fitting to assess whether m-health could be associated with better health-related outcomes for these sexual minorities. The present study examines associations between m-physical and m-mental health apps and sexual minorities' physical and mental health status in Greece. The study utilized three waves of panel data collected in 2018, 2019, and 2020. The findings indicated associations between the use of m-physical and m-mental health apps and increased physical and mental health status for sexual minorities. The work concludes that m-health could enhance informational capabilities associated with increased levels of physical and mental health for sexual minorities. Indeed, the study found that, during the COVID-19 pandemic, sexual minorities experienced physical and mental health deteriorations. Interestingly, the estimates indicated that the association between the use of m-physical and m-mental health apps and increased mental health status for sexual minorities was stronger during the COVID-19 pandemic than before. The study suggests that tracking health-related information through m-health apps during periods of increased uncertainty could be associated with better health prevention and management. If m-health apps can alleviate adverse physical and mental health symptoms for sexual minorities, their potential should be considered.
Keywords: I1; I14; O3; 330; m-Health; Smartphone; Apps; Physical Health; Mental Health; COVID-19; Sexual Minorities